Hyper-Oxygenation Attenuates the Rapid Vasodilatory Response to Muscle Contraction and Compression - Messere, Alessandro; Tschakovsky, Michael; Seddone, Stefano; Lulli, Gabriella; Franco, Walter; Maffiodo, Daniela; Ferraresi, Carlo; Roatta, Silvestro (Frontiers in Physiology, 2018)
A single muscle compression (MC) with accompanying hyperemia and hyper-oxygenation results in attenuation of a subsequent MC hyperemia, as long as the subsequent MC takes place when muscle oxygenation is still elevated. Whether this is due to the hyper-oxygenation, or compression-induced de-activation of mechano-sensitive structures is unclear. We hypothesized that increased oxygenation and not de-activation of mechano-sensitive structures was responsible for this attenuation and that both compression and contraction-induced hyperemia attenuate the hyperemic response to a subsequent muscle contraction, and vice-versa. Protocol-1) In 8 subjects two MCs separated by a 25-s interval were delivered to the forearm without or with partial occlusion of the axillary artery, aimed at preventing hyperemia and increased oxygenation in response to the first MC. Tissue oxygenation (oxygenated [hemoglobin + myoglobin]/ total [hemoglobin + myoglobin]) from forearm muscles and brachial artery blood flow were continuously monitored by means of spatially-resolved near-infrared spectroscopy and Doppler ultrasound, respectively. With unrestrained blood flow, the hyperemic response to the second MC was attenuated, compared to the first (5.7 ± 3.3 vs 14.8 ± 3.9 ml, P<0.05). This attenuation was abolished with partial occlusion of the axillary artery (14.4 ± 3.9 ml). Protocol-2) In 10 healthy subjects, hemodynamic changes were assessed in response to MC and electrically stimulated contraction (ESC, 0.5-s duration, 20 Hz) of calf muscles, as single stimuli or delivered in sequences of two separated by a 25-s interval. When MC or ESC were delivered 25 s following MC or ESC the response to the second stimulus was always attenuated (range: 60-90%). These findings support a role for excess tissue oxygenation in the attenuation of mechanically-stimulated rapid dilation and rule out inactivation of mechano-sensitive structures. Furthermore, both MC and ESC rapid vasodilatation are attenuated by prior transient hyperemia, regardless of whether the hyperemia is due to MC or ESC. Previously, mechanisms responsible for this dilation have not been considered to be oxygen sensitive. This study identifies muscle oxygenation state as relevant blunting factor, and reveals the need to investigate how these feedforward mechanisms might actually be affected by oxygenation.